Silicon negative electrode material, preparation method and application thereof, silicon negative electrode pole piece and lithium ion battery

By using micron-scale silicon powder and lithium-containing components to modify the fiber-like lithium silicate structure in the preparation process of nano-silicon, the problems of low first-effect and poor cycle stability caused by nano-silicon oxidation are solved, and efficient and low-cost silicon negative electrode material preparation is achieved.

CN119864408APending Publication Date: 2025-04-22CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311360187.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-19
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

Silicon oxide impurities are generated in the existing nano-silicon preparation process, resulting in low first efficiency and poor cycle stability of silicon materials.

Method used

Micron-scale silicon powder and lithium-containing components are dispersed in a solvent, and lithium-containing components are formed to form a nano-silicon precursor modified by grinding, and sintered in an inert atmosphere to form a structure of fibrous lithium silicate on the surface of the nano-silicon.

Benefits of technology

The phenomenon of nano-silicon oxidation is effectively avoided, the discharge capacity and Coulomb efficiency of the first circle of the silicon material are improved, the circulation performance is enhanced, and the process is simple and the cost is low.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119864408A_ABST
    Figure CN119864408A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, and provides a silicon negative electrode material and a preparation method thereof, a silicon negative electrode pole piece and a lithium ion battery. The silicon negative electrode material comprises nano silicon and fibrous lithium silicate for modifying the surface of the nano silicon. According to the preparation method of the silicon negative electrode material provided by the invention, crushing and surface modification of nano silicon particles are realized through a one-step method, the problems of low initial efficiency and poor cycling stability of a silicon material caused by silicon oxide impurities generated in an existing nano silicon preparation process are effectively solved, and the preparation method has the advantages of simple preparation process, low cost and convenience in large-scale production; when the prepared silicon negative electrode material is applied to the lithium ion battery, the first effect and the cyclicity are obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery technology, and more specifically, to a silicon negative electrode material and a preparation method thereof, a silicon negative electrode sheet, and a lithium electronic battery. Background Art

[0002] Silicon material is an ideal choice to replace graphite as an electrode plate because of its high theoretical specific capacity. However, silicon material will undergo volume expansion of up to 300% during the charging and discharging process, resulting in pulverization and shedding of the material, which seriously affects its cycle performance. In view of this, researchers often use nano-silicon and carbon to compound to alleviate the volume expansion problem of silicon materials, improve the conductivity of the material, and thus improve the battery cycle performance. Among them, the preparation methods of nano-silicon mainly include chemical vapor deposition, magnesium thermal reduction, sol-gel, physical grinding, etc. Among them, the use of a grinder to grind micron-sized silicon powder to prepare nano-silicon is a more efficient and economical method. However, during the high-energy grinding process, nano-silicon will react with oxygen to generate SiO x The presence of the oxide layer will reduce the first-cycle coulomb efficiency (first efficiency) of the material, so HF or NaOH is generally required to etch the nano-silicon.

[0003] Patents CN108269979A and CN109786733A use silicon oxide to sinter with inorganic compounds of lithium at high temperature to obtain silicon oxide / silicon / lithium metasilicate composite materials that can be used as negative electrode materials for lithium-ion batteries. However, the cost of using silicon oxide as a raw material is high, and the silicon content obtained by high-temperature reaction of silicon oxide is low, resulting in a low specific capacity of the composite material.

[0004] The invention patent with patent number CN106252638B provides a method for preparing a silicon / lithium silicate / oxide composite negative electrode material with a lithium silicate interface layer, which uses a method combining chemical precipitation with high-temperature solid-phase reaction, and uses the high adsorption performance of the precipitation reaction product to adsorb excess lithium ions, so that it reacts with trace silicon oxide on the silicon surface in a high-temperature solid-phase reaction to form a lithium silicate interface layer in situ between the silicon active center and the oxide matrix. This method uses nano-silicon powder as the active raw material, which is costly; and the use of chemical precipitation method will result in low efficiency.

[0005] Patents CN112186188A and CN114242962A both provide a method for preparing a silicon-based negative electrode material with a three-layer structure of silicon / lithium silicate / carbon coating. Both methods utilize silicon and oxygen to react to produce a layer of silicon dioxide on the surface of silicon particles, then react lithium salt with silicon dioxide, and finally coat with a layer of carbon. In the above two methods, silicon needs to be oxidized on the surface to form silicon dioxide, which is a cumbersome process and expensive, and both methods introduce a relatively low-capacity carbon coating, which will affect the initial effect of the silicon material.

[0006] Therefore, it is very meaningful to develop a nano-silicon with simple process, low cost and no silicon oxide impurities on the surface as a silicon negative electrode material. Summary of the invention

[0007] The purpose of the present invention is to provide a silicon negative electrode material and a preparation method thereof, so as to solve the technical problem in the prior art that silicon oxide impurities are generated in the existing nano-silicon preparation process, resulting in low initial efficiency and poor cycle stability of silicon materials.

[0008] To achieve the above object, the technical solution adopted by the present invention is:

[0009] In a first aspect, the present invention provides a silicon negative electrode material, comprising nano-silicon and fibrous lithium silicate modifying the surface of the nano-silicon.

[0010] According to some embodiments of the present invention, the fibrous lithium silicate does not completely cover the surface of the nano-silicon.

[0011] According to some embodiments of the present invention, the median particle size of the silicon negative electrode material is 150 to 300 nm.

[0012] According to some embodiments of the present invention, the length of the fibrous lithium silicate is 5 to 20 nm.

[0013] According to some embodiments of the present invention, the first cycle discharge capacity of the silicon negative electrode material is greater than 2000 mAh / g.

[0014] According to some embodiments of the present invention, the first cycle discharge capacity of the silicon negative electrode material is 2020-2300 mAh / g.

[0015] According to some embodiments of the present invention, the first coulombic efficiency of the silicon negative electrode material is greater than 88%.

[0016] According to some embodiments of the present invention, after 50 cycles, the capacity retention rate of the silicon negative electrode material is >70%, preferably >80%.

[0017] In a second aspect, the present invention provides a method for preparing a silicon negative electrode material, comprising: dispersing micron-sized silicon powder and a lithium-containing component in a solvent to obtain a mixed liquid, grinding the mixed liquid to obtain a lithium silicate-modified nano-silicon precursor, and then sintering the lithium silicate-modified nano-silicon precursor in an inert atmosphere to obtain a silicon negative electrode material.

[0018] The preparation method of the silicon negative electrode material provided by the present invention uses cheap micron-sized silicon powder as raw material. In the process of grinding and crushing the micron-sized silicon powder into nano-silicon, silicon gradually reacts with water to generate silicic acid, and directly reacts with lithium salt to generate lithium silicate, which can not only effectively avoid the oxidation of nano-silicon into inactive silicon oxide in the process of crushing micron-sized silicon into nano-silicon, resulting in a decrease in the capacity and coulomb efficiency of the silicon material; but also can form fibrous lithium silicate on the surface of nano-silicon. Since lithium silicate has excellent lithium ion conductivity and a stable structure, it can effectively improve the electrochemical properties of silicon materials, alleviate volume expansion, and improve cycle performance. The silicon negative electrode material provided by the present invention can be used alone to prepare negative electrode plates, without the need to alleviate the volume expansion problem by compounding with carbon.

[0019] According to some embodiments of the present invention, the solvent is an alcohol-water mixture.

[0020] According to some embodiments of the present invention, the concentration of the alcohol component in the alcohol-water mixture is 50-80 vol%. If the concentration of the alcohol component in the alcohol-water mixture is too low, the reaction process of generating lithium silicate may be uncontrollable, making it difficult to generate a fibrous structure.

[0021] According to some embodiments of the present invention, the alcohol component in the alcohol-water mixture includes at least one of methanol, ethanol and ethylene glycol.

[0022] In the present invention, the grinding medium (solvent) in the grinding process adopts an alcohol-water mixture, which can limit the efficiency of silicon reacting with water to generate silicic acid, and is conducive to the uniform distribution of lithium silicate in fibrous form on the surface of nano-silicon, which can effectively improve the initial efficiency and cycle performance of silicon materials.

[0023] According to some embodiments of the present invention, the sintering process includes: first heating the temperature to 150-300°C at a heating rate of 0.1-1°C / min, and keeping the temperature for 1-3 hours; then heating the temperature to 650-900°C at a heating rate of 1-10°C / min, and keeping the temperature for 1-5 hours.

[0024] In the present invention, the sintering process adopts the above-mentioned staged temperature control, which is conducive to achieving uniform distribution of fibrous lithium silicate on the surface of nano-silicon, and can effectively improve the first efficiency and cycle performance of silicon materials.

[0025] According to some embodiments of the present invention, the median particle size of the micron-sized silicon powder is 1 to 100 μm.

[0026] According to some embodiments of the present invention, the purity of the micron-sized silicon powder is above 99.0%.

[0027] According to some embodiments of the present invention, the lithium-containing component includes at least one of lithium hydroxide, lithium carbonate, and lithium bicarbonate.

[0028] According to some embodiments of the present invention, the mass ratio of the micron-sized silicon powder to the lithium-containing component is 1:0.005-0.05.

[0029] According to some embodiments of the present invention, the pH of the mixed solution is controlled at 11 to 14. The pH of the mixed solution can be adjusted by adding an acid-base regulator (such as ammonia water) to the mixed solution, so that the mixed solution is in an alkaline state to ensure that the reaction between silicon and water generates silicic acid.

[0030] According to some embodiments of the present invention, the inert atmosphere includes a nitrogen atmosphere or an inert gas atmosphere.

[0031] In the present invention, the equipment and specific process used in the grinding process can adopt existing commonly used equipment and process, as long as it can achieve the goal of crushing micron-sized silicon powder into relatively uniform nano-silicon.

[0032] According to some embodiments of the present invention, the grinding balls used in the grinding process are zirconium oxide grinding balls.

[0033] According to some embodiments of the present invention, the diameter of the grinding ball is 0.1-1 mm.

[0034] According to some embodiments of the present invention, the grinding process is performed at a rotation speed of 1500 to 3000 rpm and for a time of 2 to 6 hours.

[0035] According to some embodiments of the present invention, the mass ratio of the micron-sized silicon powder to the solvent is 5 to 30:100.

[0036] According to some embodiments of the present invention, the lithium silicate-modified nano-silicon precursor is first separated and dried, and then sintered.

[0037] According to some embodiments of the present invention, the separation is centrifugal separation.

[0038] According to some embodiments of the invention, the drying is freeze-drying.

[0039] In a third aspect, the present invention provides a silicon negative electrode material prepared by the preparation method described in the second aspect.

[0040] In a fourth aspect, the present invention provides a silicon negative electrode plate, comprising a current collector and the silicon negative electrode material described in the first aspect or the silicon negative electrode material described in the third aspect coated on the surface of the current collector.

[0041] According to some embodiments of the present invention, the silicon negative electrode material is mixed with a conductive material and an adhesive and then coated on the surface of the current collector.

[0042] In a fifth aspect, the present invention provides the use of the silicon negative electrode material described in the first aspect, the silicon negative electrode material described in the third aspect, or the silicon negative electrode plate described in the fourth aspect in a lithium-ion battery.

[0043] In a sixth aspect, the present invention provides a lithium-ion battery comprising the silicon negative electrode sheet described in the fourth aspect.

[0044] According to some embodiments of the present invention, the lithium-ion battery further comprises a positive electrode sheet containing lithium, a separator and an electrolyte.

[0045] According to some embodiments of the present invention, the lithium ion battery is a liquid lithium ion battery, a semi-solid lithium ion battery or an all-solid lithium ion battery.

[0046] The beneficial effects of the present invention are at least:

[0047] The preparation method of the silicon negative electrode material provided by the present invention realizes the crushing and surface modification of nano-silicon particles through a one-step method, effectively solving the problem that the silicon oxide impurities generated in the existing nano-silicon preparation process lead to low initial efficiency and poor cycle stability of silicon materials, and has the advantages of simple preparation process, low cost, and easy large-scale production; the prepared silicon negative electrode material is applied to lithium-ion batteries, and its initial efficiency and cyclability are significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 This is the SEM image of the silicon negative electrode material of Example 1.

[0049] Figure 2 This is the TEM image of the silicon negative electrode material of Example 1.

[0050] Figure 3 This is the EDS image of the silicon negative electrode material of Example 1.

[0051] Figure 4 This is the X-ray diffraction pattern of the silicon negative electrode material of Example 1.

[0052] Figure 5 The cyclic stability test curves of the silicon negative electrode materials of Examples 1-3 and Comparative Example 1.

[0053] Figure 6 This is the SEM image of the silicon negative electrode material of Comparative Example 1.

[0054] Figure 7 This is the SEM image of the silicon negative electrode material of Comparative Example 3. DETAILED DESCRIPTION

[0055] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in combination with specific implementation methods. It should be understood that the specific implementation methods described herein are only used to explain this patent in detail and do not limit the scope of protection of the present invention in any way.

[0056] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the raw materials, instruments and equipment used in the following examples, etc., can all be purchased on the market or can be obtained by existing methods; the reagent amounts, unless otherwise specified, are the reagent amounts used in conventional experimental operations; the experimental methods, unless otherwise specified, are all conventional methods.

[0057] In each embodiment and comparative example of the present invention, each performance data is tested according to the following test method:

[0058] In the present invention, a scanning electron microscope (SEM) is used to characterize the material morphology. Specifically, the instrument model used is a German ZEISS-MERLIN high-resolution field emission scanning electron microscope, and the test conditions are: the sample is directly pressed on a sample stage containing a conductive tape, and then inserted into the electron microscope for observation; the acceleration voltage is 3kV, the current is 30pA, the magnification is 500-5000 times, and the sample can be switched to the Mapping mode for EDS test analysis.

[0059] In the present invention, a transmission electron microscope (TEM) from FEI-Tecnai, USA, is used to further characterize the morphology of the material. Test conditions: The sample is placed on a copper support mesh and then inserted into an electron microscope for observation.

[0060] In the present invention, the LAND battery test system is used to test the electrochemical performance. The test method includes: applying a slurry of negative electrode material, conductive carbon black and adhesive in a ratio of 8:1:1 on copper foil to form a pole piece, and the pole piece surface density is 50-100 mg / cm 2 The test temperature was 25°C. The materials of the embodiments and comparative examples and metal lithium sheets were used as the positive and negative electrodes of the battery, 1 mol / L LiPF6 solution was used as the electrolyte, and a polypropylene microporous membrane was used as the separator. The battery was assembled into a CR2016 button battery. The charge and discharge rate of the first three cycles was 0.05C, and the voltage range was 0.005V to 1.5V; the cycle charge and discharge rate was 0.2C, and the voltage range was 0.005V to 1.5V.

[0061] In the present invention, the D / max-2200 / PC X-ray diffractometer of Rigaku Corporation of Japan is used to perform XRD analysis on the prepared ternary positive electrode material. The analysis test conditions are: 2θ angle test range 10°-70°, scanning speed 6° / min. Test tube voltage 40KV, current 40mA, Cu-Kα ray source.

[0062] Example 1

[0063] Take 2g of lithium hydroxide and add it to 1000g of 60v% ethanol aqueous solution, stir to dissolve completely, test the solution pH = 13, then add 200g of silicon powder (particle size 80μm, purity 99.0%), stir and mix evenly, the slurry enters a sand mill for cyclic grinding, the grinding beads in the sand mill are 0.3mm zirconium oxide grinding balls, the grinding speed is 2800rpm, the grinding time is 4h, the slurry is transferred out, the supernatant is removed by centrifugation, the lower layer of slurry is placed in a freeze dryer, and dried completely to obtain a lithium silicate modified nano-silicon precursor.

[0064] The lithium silicate modified nano-silicon precursor was subjected to the following programmed temperature sintering treatment: in a nitrogen atmosphere, the temperature was raised to 250°C at a rate of 0.2°C / min and kept at that temperature for 2 hours; then the temperature was raised to 800°C at a rate of 5°C / min and kept at that temperature for 2 hours; after cooling, the silicon negative electrode material was obtained. The median particle size of the obtained silicon negative electrode material was 200nm.

[0065] The SEM image of the silicon negative electrode material prepared in this embodiment is as follows: Figure 1 As shown, it can be seen that the fibrous lithium silicate is evenly arranged on the surface of nano-silicon.

[0066] The TEM image of the silicon negative electrode material prepared in this embodiment is as follows: Figure 2 As shown, it can be seen that the fibrous lithium silicate grows sequentially on the surface of nano-silicon, and the length of the fibrous lithium silicate is 10 nm.

[0067] The EDS spectrum distribution diagram of the silicon negative electrode material prepared in this embodiment is as follows: Figure 3 As shown, it can be seen that the silicon surface is uniformly coated with lithium and oxygen elements, indicating that a lithium-oxygen-silicon compound is formed on the silicon surface, proving the existence of lithium silicate, that is, the surface of the nano-silicon is coated with lithium silicate material.

[0068] The X-ray diffraction pattern of the silicon negative electrode material prepared in this embodiment is as follows: Figure 4 As shown, it can be seen that the diffraction peak of the material is consistent with the PDF card of pure silicon, indicating that its main component is silicon.

[0069] After the battery is made of the silicon negative electrode material prepared in this embodiment, the cycle stability test curve at 0.2C charge and discharge current is shown in FIG. Figure 5 .from Figure 5 It can be seen that the first cycle discharge capacity of the silicon negative electrode material prepared in this embodiment is 2128 mAh / g, the first coulombic efficiency is 92%, and after 50 cycles, the capacity retention rate is greater than 89%.

[0070] Example 2

[0071] Take 2.5g of lithium carbonate and 3g of concentrated ammonia water and add them to 1000g of 50v% methanol aqueous solution, stir and dissolve completely, test the solution pH = 14, then add 50g of silicon powder (particle size is 100μm, purity is 99.5%), stir and mix evenly, the slurry enters the sand mill for cyclic grinding, the grinding beads in the grinder are selected as 1mm zirconium oxide grinding balls, the grinding speed is 3000rpm, the grinding time is 6h, the slurry is transferred out, the supernatant is removed by centrifugation, the lower layer of slurry is placed in a freeze dryer, and dried completely to obtain a lithium silicate modified nano-silicon precursor.

[0072] The lithium silicate modified nano-silicon precursor was subjected to the following programmed temperature sintering process: the temperature was raised to 300°C at a rate of 0.5°C / min in a nitrogen atmosphere, and kept at that temperature for 1 hour; then the temperature was raised to 900°C at a rate of 10°C / min, and kept at that temperature for 1 hour; after cooling, the silicon negative electrode material was obtained. The median particle size of the obtained silicon negative electrode material was 300nm.

[0073] After the battery is made of the silicon negative electrode material prepared in this embodiment, the cycle stability test curve at 0.2C charge and discharge current is shown in FIG. Figure 5 .from Figure 5 It can be seen that the first cycle discharge capacity of the silicon negative electrode material prepared in this embodiment is 2194 mAh / g, the first coulomb efficiency is 89%, and after 50 cycles, the capacity retention rate is greater than 84%.

[0074] Example 3

[0075] Take 1.5g of lithium bicarbonate and 3g of concentrated ammonia water and add them to 1000g of 80v% ethanol aqueous solution, stir and dissolve completely, test the solution pH = 11, then add 300g of silicon powder (particle size is 1μm, purity is 99.0%), stir and mix evenly, the slurry enters the sand mill for cyclic grinding, the grinding beads in the grinder are selected as 0.1mm zirconium oxide grinding balls, the grinding speed is 1500rpm, the grinding time is 2h, the slurry is transferred out, the supernatant is removed by centrifugation, the lower layer of slurry is placed in a freeze dryer, and dried completely to obtain a lithium silicate modified nano-silicon precursor.

[0076] The lithium silicate modified nano-silicon precursor was subjected to the following programmed temperature sintering process: the temperature was raised to 150°C at a rate of 1°C / min in a nitrogen atmosphere, and kept at this temperature for 3 hours; then the temperature was raised to 650°C at a rate of 1°C / min, and kept at this temperature for 5 hours; after cooling, the silicon negative electrode material was obtained. The median particle size of the obtained silicon negative electrode material was 150nm.

[0077] After the battery is made of the silicon negative electrode material prepared in this embodiment, the cycle stability test curve at 0.2C charge and discharge current is shown in FIG. Figure 5 .from Figure 5 It can be seen that the first cycle discharge capacity of the silicon negative electrode material prepared in this embodiment is 2044 mAh / g, the first coulombic efficiency is 93%, and after 50 cycles, the capacity retention rate is greater than 86%.

[0078] Comparative Example 1

[0079] The preparation method of the silicon negative electrode material is similar to that of Example 1, except that the ethanol aqueous solution is replaced with water of equal mass.

[0080] The SEM image of the silicon negative electrode material prepared in this comparative example is as follows: Figure 6 As shown, it can be seen that there is no uniform fibrous structure arrangement on the surface of nano-silicon, indicating that after changing the grinding solvent, the specific lithium silicate fibrous structure will not be formed.

[0081] After the battery is made of the silicon negative electrode material prepared in this comparative example, the cycle stability test curve at 0.2C charge and discharge current is shown in Figure 5 .from Figure 5 It can be seen that the first cycle discharge capacity of the silicon negative electrode material prepared in this comparative example is 2033mAh / g, the first coulomb efficiency is 90%, and after 50 cycles, the capacity retention rate is 65%, and the cycle stability is poor.

[0082] Comparative Example 2

[0083] The preparation method of the silicon negative electrode material refers to Example 1, except that the 80v% ethanol aqueous solution with a concentration of is replaced by a 40v% ethanol aqueous solution with a concentration of.

[0084] After the battery was made of the silicon negative electrode material prepared in this comparative example, the cycle stability test was carried out under a charge and discharge current of 0.2C. The first cycle discharge capacity of the silicon negative electrode material prepared in this comparative example was 1950mAh / g, the first coulomb efficiency was 70%, and after 50 cycles, the capacity retention rate was 55%, and the cycle stability was poor.

[0085] Comparative Example 3

[0086] The preparation method of the silicon negative electrode material refers to Example 1, except that the conditions for the programmed temperature sintering treatment are modified to: in a nitrogen atmosphere, increase the temperature to 800° C. at a heating rate of 5° C. / min and keep the temperature for 2 h.

[0087] The SEM image of the silicon negative electrode material prepared in this comparative example is as follows: Figure 7 As shown, it can be seen that there is no uniform fibrous structure arrangement on the surface of nano-silicon, indicating that after changing the heating rate, the specific lithium silicate fibrous structure will not be formed.

[0088] After the battery was made of the silicon negative electrode material prepared in this comparative example, the cycle stability test was carried out under a charge and discharge current of 0.2C. The first cycle discharge capacity of the silicon negative electrode material prepared in this comparative example was 1980mAh / g, the first coulomb efficiency was 85%, and after 50 cycles, the capacity retention rate was 50%, and the cycle stability was poor.

[0089] Comparative Example 4

[0090] The preparation method of the silicon negative electrode material refers to Example 3, except that the conditions for the programmed temperature sintering treatment are modified to: in a nitrogen atmosphere, the temperature is increased to 650° C. at a heating rate of 1° C. / min and kept at this temperature for 5 h.

[0091] After the battery was made of the silicon negative electrode material prepared in this comparative example, the cycle stability test was carried out under a charge and discharge current of 0.2C. The first cycle discharge capacity of the silicon negative electrode material prepared in this comparative example was 2010mAh / g, the first coulomb efficiency was 80%, and after 50 cycles, the capacity retention rate was 48%, and the cycle stability was poor.

[0092] It can be seen from the test results of the above embodiments and comparative examples that the silicon negative electrode material having a fibrous lithium silicate structure on the nano-silicon surface provided by the present invention can effectively alleviate the volume expansion of the silicon material during the charge and discharge process and effectively improve the cycle performance of the silicon material.

[0093] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.

Claims

1. A silicon negative electrode material, characterized in that: The invention comprises nano silicon and fibrous lithium silicate which modifies the surface of the nano silicon.

2. The silicon negative electrode material according to claim 1, characterized in that: The median particle size of the silicon negative electrode material is 150 to 300 nm; And / or, the length of the fibrous lithium silicate is 5 to 20 nm; And / or, the first cycle discharge capacity of the silicon negative electrode material is greater than 2000 mAh / g; And / or, the first coulombic efficiency of the silicon negative electrode material is greater than 88%; And / or, after 50 cycles, the capacity retention rate of the silicon negative electrode material is greater than 70%, preferably greater than 80%.

3. A method for preparing a silicon negative electrode material, characterized in that: include: Micron-sized silicon powder and lithium-containing components are dispersed in a solvent to obtain a mixed solution, the mixed solution is ground to obtain a lithium silicate-modified nano-silicon precursor, and the lithium silicate-modified nano-silicon precursor is sintered in an inert atmosphere to obtain a silicon negative electrode material.

4. The preparation method according to claim 3, characterized in that: The solvent is an alcohol-water mixture; Preferably, The concentration of the alcohol component in the alcohol-water mixture is 50-80v%; And / or, the alcohol component in the alcohol-water mixture includes at least one of methanol, ethanol and ethylene glycol.

5. The preparation method according to claim 3 or 4, characterized in that: The sintering treatment comprises: firstly heating the temperature to 150-300°C at a heating rate of 0.1-1°C / min and keeping the temperature for 1-3h; then heating the temperature to 650-900°C at a heating rate of 1-10°C / min and keeping the temperature for 1-5h.

6. The preparation method according to any one of claims 3 to 5, characterized in that: The median particle size of the micron-sized silicon powder is 1 to 100 μm; And / or, the purity of the micron-sized silicon powder is above 99.0%; And / or, the lithium-containing component includes at least one of lithium hydroxide, lithium carbonate, and lithium bicarbonate; and / or, the mass ratio of the micron-sized silicon powder to the lithium-containing component is 1:0.005-0.05; And / or, the pH of the mixed solution is controlled at 11 to 14; And / or, the inert atmosphere includes a nitrogen atmosphere or an inert gas atmosphere.

7. A silicon negative electrode material prepared by the preparation method according to any one of claims 3 to 6.

8. A silicon negative electrode plate, characterized in that: It comprises a current collector and the silicon negative electrode material according to claims 1-2 or the silicon negative electrode material according to claim 7 coated on the surface of the current collector.

9. Use of the silicon negative electrode material according to claims 1-2 or the silicon negative electrode material according to claim 7 or the silicon negative electrode plate according to claim 8 in lithium-ion batteries.

10. A lithium electronic battery comprising the silicon negative electrode sheet according to claim 8.

Citation Information

Patent Citations

  • A silicon / oxide composite anode material with a lithium silicate interface layer and its preparation method

    CN106252638B

  • Silicon monoxide / silicon / lithium metasilicate composite negative electrode material and preparation method thereof

    CN108269979A

  • Lithium-ion battery anode material, preparation method thereof and lithium-ion battery

    CN109786733A

  • Silicon-based negative electrode material and preparation method and application thereof

    CN112186188A

  • Lithium orthosilicate and carbon coated nano silicon composite material as well as preparation method and application thereof

    CN114242962A